The crucial role of external force in the estimation of the topology freezing transition temperature of vitrimers by elongational creep measurements. (9th September 2020) - Kaiser, Simon; Novak, Patrick; Giebler, Michael; Gschwandl, Mario; Novak, Philipp; Pilz, Gerald; Morak, Matthias; Schlögl, Sandra
Abstract: Vitrimers are covalent adaptable networks that rely on associative bond exchange reactions. Along with the glass transition temperature, the service temperature of thermally activated vitrimers is strongly governed by the topology freezing transition temperature ( T v ), at which the covalent bond exchange reactions become significantly fast. Despite the vast number of developed vitrimer systems, there is a serious lack in direct methods for the determination of the T v . In the present work, we highlight a versatile and facile measurement routine, which enables a precise estimation of the T v in epoxy-acid vitrimers undergoing thermo-activated transesterifications. In particular, elongational creep of the networks is measured as a function of temperature and the applied stress. The results show that the onset temperature of the plastic flow regime is clearly stress-dependent, possibly leading to an inaccuracy of T v data in the existing literature obtained from so-called dilatometry measurements. We demonstrate that with increasing external force on the specimens, the onset of macroscopic flow is gradually shifted to lower temperatures and approaches the accurate T v of the material at a particular stress level. This behaviour is found in different epoxy-acid vitrimers with varying T g . The data is in very good accordance with (theoretical) T v values, which are reported in literature and were received from stress relaxation data, confirming the validity and equivalence of the method presented. Graphical abstract: Image 1 Highlights: Vitrification transition determines the upper service temperature of vitrimers. New method for direct analysis of vitrification transition temperature established. Precise estimation of vitrification transition temperature from dilatometry. Stress-dependent onset of plastic flow in creep measurements at rising temperature. Crucial role of external force for accurate analysis of Tv in epoxy-acid vitrimers.